The pyramid plan walk out, work out, lose weight - Snowdan, Lee (Hodder and Stoughton, 1996)
Les Snowdon and Maggie Humphreys, bestselling authors of The Walking Diet, revolutionised fitness by recognising walking as the safest, most effective form of aerobic exercise that could be enjoyed by people of all ages. Now they have designed a health and fitness programme that you can adapt to suit your needs. Based on Walk Aerobics, "The Pyramid Plan" combines Pyramid Fitness with the Pyramid Diet to give you a complete personal lifestyle plan for the 90s.